A Friend in Prison: Human-Animal Bond, Stress and Self-Esteem of Detained Juveniles in Dutch Cell Dogs - Esther M. Karkdijk; Hanne M. Duindam; Maja Deković; Hanneke E. Creemers; Jessica J. Asscher (Animals, 2022)
This study examined to what extent the human–animal bond (HAB) had a positive impact on stress and self-esteem among detained juveniles participating in the prison-based dog training program Dutch Cell Dogs (DCD). Participants were 75 detained juveniles (mean age = 19.5, 86.7% male). Self-reported stress and self-esteem were assessed before the start of DCD (T1), after four weeks (halfway training/T2) and after eight weeks (end training/T3). Structured interviews and questionnaire items were used to measure the HAB quality and perceived reciprocity in the HAB at T2 and T3. Data were analyzed using Structural Equation Modeling. In the variable-centered approach analyses, only the cross-sectional positive association between HAB quality and self-esteem at T2 was significant in the cross-lagged panel models. None of the cross-lagged paths between the HAB and stress or self-esteem were significant. In the person-centered approach analyses, growth mixture modeling identified two patterns of self-esteem (“high stable” and “high decreasing”); however, these patterns were not predicted by HAB. Thus, in contrast to our hypotheses, the HAB did not predict improvements in detained juveniles’ stress and self-esteem. These findings underline the need for more research into the often-presumed role of HAB within prison-based dog training programs.